THE PAYMENT REFORM INITIATIVE TO REDUCE AVOIDABLE HOSPITALIZATIONS AMONG NURSING FACILITY RESIDENTS: AN OVERVIEW. (11th November 2018) - Ingber, M; Feng, Z; Khatutsky, G; Bercaw, L E; Segelman, M; Tracy Zheng, N; Li, Q; Wang, J M
Abstract: This presentation will provide an overview of the CMS Initiative to Reduce Avoidable Hospitalizations among Nursing Facility Residents—Payment Reform. The Initiative provides enhanced Medicare Part B payments to participating nursing facilities and practitioners as incentives to reduce hospitalizations among long-stay residents. Six Enhanced Care and Coordination Provider (ECCP) organizations each partner with two separate groups of participating facilities from seven states. The "Payment-only" group includes 144 facilities newly recruited and eligible only for the new payments. The "ECCP + Payment" group includes 107 "legacy" facilities which participated in the first phase of the Initiative for clinical and educational interventions and now also receive the new payments.